1998
DOI: 10.1016/s0370-2693(98)00221-4
|View full text |Cite
|
Sign up to set email alerts
|

A potential infrared problem with the damping rates for gluons with soft momentum in hot QCD

Abstract: We calculate the damping rate γ l for longitudinal gluons with zero momentum in finite high temperature QCD and show that some of its contributing terms are infrared divergent. This is in contrast with the expectation that this damping rate is to be equal to the corresponding one γ t for transverse gluons which is known to be finite. Our calculation was motivated by the fact that similar divergent terms occur when we calculated in a previous work γ t to order p 2 , p being the momentum of the gluon. After we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 4 publications
(13 reference statements)
2
31
0
Order By: Relevance
“…However, as will be discussed further below, the limit k → 0 involves infrared problems, and there are even explicit calculations [322,323] that claim to find obstructions to this equality, which are however contradicted by the recent work of [324].…”
Section: Long-wavelength Plasmon Dampingmentioning
confidence: 99%
“…However, as will be discussed further below, the limit k → 0 involves infrared problems, and there are even explicit calculations [322,323] that claim to find obstructions to this equality, which are however contradicted by the recent work of [324].…”
Section: Long-wavelength Plasmon Dampingmentioning
confidence: 99%
“…This was first indicated in [4], where the direct and explicit attempt to calculate the damping rate for non-moving longitudinal gluons showed that it is infrared divergent. The infrared sensitivity occurs in other quantities too [5,6].…”
Section: Introductionmentioning
confidence: 89%
“…In a line of works, we have used this formalism and looked into the infrared behavior of fully-HTL-dressed one-loop-order damping rates of slow-moving longitudinal [55,56] and transverse gluons [57], quarks [58][59][60], fermions 2 [61][62][63] and photons [64] in QED, and quasiparticles [65] in scalar QED. 3 In this logic, the natural step forward is to try to calculate the NLO energies of the quasiparticles.…”
Section: Jhep03(2015)058mentioning
confidence: 99%